Оптимизация пенсионной системы - Боровский, В.Н.; Лазарев, В.А. (Культура народов Причерноморья, 2013)
В статье рассмотрены основные проблемы пенсионной системы, перспективы и направления ее
развития и реформирования.
Дан краткий анализ современного состояния бюджета Пенсионного фонда и его роль в пенсионном обеспечении
граждан, оценка и прогнозирование расходов бюджета по функциональному назначению, анализ обязательного
государственного социального страхования граждан в Украине. У статті розглянуті основні проблеми пенсійної системи, перспективи і напряму її розвитку і
реформування.
Даний короткий аналіз сучасного стану бюджету Пенсійного фонду і його роль в пенсійному забезпеченні
громадян, оцінка і прогнозування витрат бюджету по функціональному призначенню, аналіз обов'язкового
державного соціального страхування громадян в Україні. The basic problems of the pension system, prospect and direction of its development and reformation are
considered in the article.
The short analysis of the modern state of budget of pension a fund and his role is given in the pension providing of citizens,
estimation and prognostication of charges of budget on the functional setting, analysis of obligatory state social security of
citizens in Ukraine.
By creation of off-budget social funds it was assumed to release the resource providing of social sphere from dependence of
budget, narrow-mindedness of profits of which especially painfully told on industries, financed in an estimate order from the
different links of the budgetary system.
The primary purpose of creation of funds was providing of stability, plenitude and timeliness of forming of social necessities
of population, guarantees of his major constitutional rights and strengthening of mechanism of social defence.
Gradually, in sequence, away from the budgetary system the so-called off-budget funds began to move.
Dominant position in size of mobilizuemykh facilities is occupied by off-budget social funds. By plan of
legislators, off-budget social funds are independent finansovokreditnye establishments, called to provide
financing of the major programs of social development of Ukraine. To their number behave: Pension a fund, Fund ofsocial security on the temporal loss of ability to work, Fund of social security from industrial accidents and professional
diseases, Fund of social security in case of unemployment and other